2020
DOI: 10.7554/elife.57093
|View full text |Cite
|
Sign up to set email alerts
|

Whole-organism behavioral profiling reveals a role for dopamine in state-dependent motor program coupling in C. elegans

Abstract: Animal behaviors are commonly organized into long-lasting states that coordinately impact the generation of diverse motor outputs such as feeding, locomotion, and grooming. However, the neural mechanisms that coordinate these distinct motor programs remain poorly understood. Here, we examine how the distinct motor programs of the nematode C. elegans are coupled together across behavioral states. We describe a new imaging platform that permits automated, simultaneous quantification of each of the main C… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
84
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 72 publications
(96 citation statements)
references
References 82 publications
4
84
0
Order By: Relevance
“…In contrast, dopaminergic neurons are thought to be activated by the presence of bacterial food and the release of dopamine controls the animal's roaming speed (Sawin et al 2000;Stern et al 2017). In addition, dopamine release during roaming increases the animal's egg-laying rate, so that animals display higher egg-laying rates during roaming vs. dwelling, which allows them to disperse their eggs across a food source (Cermak et al 2020). The fact that multiple biogenic amines and neuropeptides are required for the proper expression of roaming and dwelling states suggests that these states are specified by the combinatorial action of many neuromodulators.…”
Section: Roaming and Dwelling Statesmentioning
confidence: 99%
“…In contrast, dopaminergic neurons are thought to be activated by the presence of bacterial food and the release of dopamine controls the animal's roaming speed (Sawin et al 2000;Stern et al 2017). In addition, dopamine release during roaming increases the animal's egg-laying rate, so that animals display higher egg-laying rates during roaming vs. dwelling, which allows them to disperse their eggs across a food source (Cermak et al 2020). The fact that multiple biogenic amines and neuropeptides are required for the proper expression of roaming and dwelling states suggests that these states are specified by the combinatorial action of many neuromodulators.…”
Section: Roaming and Dwelling Statesmentioning
confidence: 99%
“…daf-7 expression in ASJ is also positively regulated by satiety, thus allowing it to serve as a signal that integrates multiple internal cues to promote exploration. Increased motion through bacterial lawns during roaming states also activates dopamine signaling via the dopaminergic PDE neurons that appear to integrate the presence of food with the animal's own motion (Cermak et al, 2020). Activation of dopaminergic neurons during roaming elevates egg-laying rates, allowing animals disperse their eggs across bacterial food sources.…”
Section: Bacterial Food and Internal Statementioning
confidence: 99%
“…changes in cholinergic and GABAergic signaling due to D2 antagonism (Krum et al, 2020). Furthermore, it was also shown that changes in DA may affect GABAergic egg release in the worms (Cermak et al, 2020). These results demonstrate that further research into these pathways is necessary, but this is beyond the scope of our study.…”
Section: Discussionmentioning
confidence: 72%